Effect of body fat reserves and their variation during lactation on ovarian activity resumption after a spring lambing in Rasa Aragonesa ewes. - Abecia J.A.; Forcada F.; Zaragoza L.; Castrillo C. (Body condition of sheep and goats: Methodological aspects and applications, 1995)
Sixty-one Rasa Aragonesa ewes lambing in spring were used to determine the effect of body fat reserves -measured by deuterium oxide- and liveweight on the resumption of sexual activity and ovulation rate after weaning. A 2x2 factorial design was applied, ewes being divided into two nutritional groups (high and low) during lactation and after weaning. There were no significant differences in the length of the interval weaning-first oestrus (114 days, August 15). The deuterium oxide dilution was used to assess changes in body fat content, but was not effective in very depleted ewes. The ovulation rate of ewes fed at high level before and after weaning was higher than in the other groups.
Seminar of the Working Group on Body Condition of Sheep and Goats of the FAO/CIHEAM Network on Sheep and Goats, 24-31 Mar 1994, Zaragoza (Spain)